2013
DOI: 10.1002/hup.2310
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nicotine dependence and the endophenotype‐related trait of cognitive function but not acoustic startle reponses in Japanese patients with schizophrenia

Abstract: Nicotine dependence might influence the level of verbal memory and executive function in schizophrenia patients. In addition, rs755203 and rs1044397 in CHRNA4 might play a role in the pathophysiology of nicotine dependence in healthy controls in the Japanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
1
2
Order By: Relevance
“…We confirmed previous reports of increased FTND scores in patients with schizophrenia compared to healthy individuals [ 34 , 37 ] and increased frequency of heavy smoking compared with general population [ 3 ]. However, our findings disagree with similar prevalence of heavy smoking and FTND score in healthy persons and first-episode patients [ 10 ], and with even higher FTND scores in healthy controls [ 38 ]. The differences might be related to age, since the prevalence of smoking in patients with schizophrenia increases with age [ 5 , 39 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We confirmed previous reports of increased FTND scores in patients with schizophrenia compared to healthy individuals [ 34 , 37 ] and increased frequency of heavy smoking compared with general population [ 3 ]. However, our findings disagree with similar prevalence of heavy smoking and FTND score in healthy persons and first-episode patients [ 10 ], and with even higher FTND scores in healthy controls [ 38 ]. The differences might be related to age, since the prevalence of smoking in patients with schizophrenia increases with age [ 5 , 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Those findings contrast previous reports of lower negative symptom severity in patients with higher levels of nicotine dependence [ 57 60 ] and positive correlations between FTND and PANSS negative scale, and several PANSS general items [ 61 ]. Our results are in line with other authors who observed no correlations between FTND total score [ 38 ], presence of severe nicotine dependence [ 30 ] and number of cigarettes per day [ 10 ], with any of PANSS items.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations